Impact of lung cancer screening results on participant health‐related quality of life and state anxiety in the National Lung Screening Trial. Issue 21 (25th July 2014) - Gareen, Ilana F.; Duan, Fenghai; Greco, Erin M.; Snyder, Bradley S.; Boiselle, Phillip M.; Park, Elyse R.; Fryback, Dennis; Gatsonis, Constantine
Abstract : BACKGROUND: Low‐dose computed tomography (LDCT) lung screening has been associated with a 20% reduction in lung cancer mortality. A major barrier to the adoption of lung screening is the potential negative psychological impact of a false‐positive (FP) screen, occurring in 20% to 50% of those screened. The objective of this study was to assess the impact of abnormal findings on health‐related quality of life (HRQoL) and anxiety in the American College of Radiology (ACRIN)/National Lung Screening Trial (NLST). METHODS: The NLST was a randomized screening trial comparing LDCT with chest X‐ray screening (CXR). This study was part of the original protocol. A total of 2812 participants at 16 of 23 ACRIN sites who had baseline HRQoL assessments were asked to complete the Short Form‐36 and the State Trait Anxiety Inventory (form Y‐1) questionnaires to assess short‐term (1 month) and long‐term (6 months) effects of screening. FP were lung cancer–free at 1 year, and true‐positives (TP) were not. RESULTS: Of the total participants, 1024 (36.4%) participants were FP, 63 (2.2%) were TP, 344 (12.2%) had significant incidental findings (SIFs), and 1381 (49.1%) had negative screens. Participants had been randomized to LDCT (n = 1947) and CXR (n = 865). Short‐term and long‐term HRQoL and state anxiety did not differ across participants with FP, SIF, or negative screens. Short‐term and long‐term HRQoL were lower and anxiety was higher for TP participants compared to participants with FP, SIF, and negative screens. CONCLUSIONS: In a large multicenter lung screening trial, participants receiving a false‐positive or SIF screen result experienced no significant difference in HRQoL or state anxiety at 1 or at 6 months after screening relative to those receiving a negative result. Cancer 2014;120:3401–3409. © 2014 The Authors. Cancer published by Wiley Periodicals, Inc. on behalf of American Cancer Society . Abstract : In a large multi‐center lung screening trial, participants receiving a false positive or significant incidental finding screen result experienced no significant difference in health related quality of life or state anxiety at 1 or at 6 months after screening relative to those receiving a negative result.